Factors of using e-learning in higher education and its impact on student learning - Zulherman Zulherman; Farah Mohamad Zain; Siti Nazuar Sailin (International Journal of Evaluation and Research in Education (IJERE), 2023)
This research was conducted to evaluate the adoption of e-learning in higher education and its impact on students. The quantitative research design was used in this study, and the technology acceptance model (TAM) was used with two external variables perceived enjoyment (PEN) and perceived self-efficacy (PSE), to analyze the validity and reliability of items and to test the hypotheses. This study was conducted among 592 undergraduate students who were selected using a random sampling technique. The findings of this study have successfully proven all ten hypotheses. It was evident that the students enjoyed e-learning’s adoption, which had succeeded in increasing students’ motivation to learn, increasing students’ confidence, and expanding students’ knowledge.